Intracellular mechanisms of fungal space searching in microenvironments - Held, Marie; Kašpar, Ondřej; Edwards, Clive; Nicolau, Dan V (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Filamentous fungi that colonize microenvironments, such as animal or plant tissue or soil, must find optimal paths through their habitat, but the biological basis for negotiating growth in constrained environments is unknown. We used time-lapse live-cell imaging of Neurospora crassa in microfluidic environments to show how constraining geometries determine the intracellular processes responsible for fungal growth. We found that, if a hypha made contact with obstacles at acute angles, the Spitzenkörper (an assembly of vesicles) moved from the center of the apical dome closer to the obstacle, thus functioning as an internal gyroscope, which preserved the information regarding the initial growth direction. Additionally, the off-axis trajectory of the Spitzenkörper was tracked by microtubules exhibiting "cutting corner" patterns. By contrast, if a hypha made contact with an obstacle at near-orthogonal incidence, the directional memory was lost, due to the temporary collapse of the Spitzenkörper-microtubule system, followed by the formation of two "daughter" hyphae growing in opposite directions along the contour of the obstacle. Finally, a hypha passing a lateral opening in constraining channels continued to grow unperturbed, but a daughter hypha gradually branched into the opening and formed its own Spitzenkörper-microtubule system. These observations suggest that the Spitzenkörper-microtubule system is responsible for efficient space partitioning in microenvironments, but, in its absence during constraint-induced apical splitting and lateral branching, the directional memory is lost, and growth is driven solely by the isotropic turgor pressure. These results further our understanding of fungal growth in microenvironments relevant to environmental, industrial, and medical applications.
Keywords: životní prostředí; mikrotubuly; Environment; časosběrné zobrazování; Hyphae; hyfy; Microtubules; Time-Lapse Imaging; optické zobrazování; Neurospora crassa; Optical Imaging